Peningkatan Keterampilan Menulis Teks Deskripsi Menggunakan Strategi Think Talk Write (TTW) di Kelas IV SDN 10 Batu Taba Kabupaten Tanah Datar - Febrianti, Dilla; Alwi, Nur Azmi (TSAQOFAH, 2025)
This study is motivated by the low writing skills of students due to a teacher-centered learning approach and the lack of active student participation. The aim of this research is to describe the improvement of students' writing skills through the Think Talk Write (TTW) strategy in grade IV at SDN 10 Batu Taba, Tanah Datar Regency. This research employs the Classroom Action Research (CAR) method with qualitative and quantitative approaches conducted in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of the research include the researcher as a practitioner, the class teacher as an observer, and 16 grade IV students. Data collection techniques involve observation, tests, and non-tests. The results indicate an improvement in various aspects. First, the planning of teaching modules increased from 89.58% (B) in cycle I to 95.8% (SB) in cycle II. Second, the implementation of learning by the teacher improved from 91% to 96.4%, and third, student activity also increased from 91% to 96.4%, both categorized as very good. Fourth, the results of students' writing skills improved from an average of 73.96 (C) to 84.57 (B). Fifth, knowledge scores increased from 76 (C) to 91.25 (SB). Thus, the Think Talk Write strategy has proven to be effective in improving students' writing skills in grade IV.